Impact of a Youth-Focused Care Model on Retention and Virologic Suppression Among Young Adults With HIV Cared for in an Adult HIV Clinic. (1st February 2019) - Griffith, David; Snyder, Jeremy; Dell, Shanna; Nolan, Kisten; Keruly, Jeanne; Agwu, Allison
Abstract : Background: Young adults with HIV (YAHIV) are less likely to be retained in care or achieve viral suppression (VS) when seen in adult clinics. We assessed the outcomes of a youth-focused care model versus standard of care (SOC) within a large adult HIV clinic. Setting: The Accessing Care Early (ACE) program for YAHIV is embedded within an adult clinic. Eligibility for ACE includes age 18–30 years with ≥1 criteria: transfer from pediatric care, mental health diagnosis, substance use, or identified adherence barriers. Ineligible patients receive SOC. Methods: Retrospective analysis of patients entering ACE versus SOC from 2012 to 2014. Multivariable logistic regression assessed variables associated with retention and VS <200 copies per milliliter, and in separate analysis, clinical services utilization. Results: One hundred thirty-seven YAHIV entered care (2012–2014), 61 ACE and 76 SOC. Despite higher risk factors, ACE YAHIV were less likely to be lost to follow-up compared with SOC (16% versus 37%, P < 0.01). At 24 months, 49% in ACE versus 26% in SOC met the retention measure ( P < 0.01). In adjusted analysis, ACE was associated with retention in care [AOR 3.26 (1.23–8.63)]. Of those meeting the retention measure, 60% of ACE versus 89% of SOC had VS [AOR 0.63 (0.35–1.14)]. Retention was associated with more frequent social work visits, nurse phone calls, and peer navigator interactions. Conclusions: Higher risk ACE YAHIV had better retention than SOC YAHIV in an adult clinic. Improved retention did not lead to improved VS, underscoring the need for additional interventions to optimize VS for YAHIV.